Governing by network : the new shape of the public sector - Goldsmith, Stephen, 1946- (Brookings Institution Press, 2004)
Examines for the first time the US government's transformation from centralized control over public programmes to facilitating services through networks of nongovernmental entities, as seen through the experience of dozens of public innovators.
"Innovations in American Government, John F. Kennedy School of Government, Harvard University."
Keywords: Public-private sector cooperation -- United States.; Public administration -- United States.; Contracting out -- United States.; Partenariat public-privé -- États-Unis.; Administration publique (Science) -- États-Unis.; Impartition -- États-Unis.; POLITICAL SCIENCE -- Public Affairs & Administration.; Contracting out; Public administration; Public-private sector cooperation; United States